Effects of weather on breeding success of Ashy prinia (Prinia socialis) in Manigram of Tilottama Municipality, Nepal (Nepal Journal of Environmental Science, 2020)
Breeding success of species, including nest construction to chick fledgling, is a major determining factor for the conservation of bird species. Ashy prinia (Prinia socialis), a small-sized, insectivorous bird, which is widely distributed in South East Asia is less explored for its breeding ecology. This study was performed in natural habitats of Tilottama municipality, Nepal, and the data such as nest characteristics, clutch size, activities of parents on nest were collected with regular monitoring of nest from the beginning of its construction to chicks fledgling. Ashy prinia constructed nests on bushes of shrubs and grasses using materials like grass, nylon threads, small twigs, cotton swag and some threads. The clutch size was four; and the average length and breadth of eggs were 1.6 cm and 1.2 cm, respectively. The nest was able to fledge chicks successfully, and their breeding success was 75%, determined by the activities of parents, local weather conditions mainly cloud cover, temperature and wind.  In addition, the breeding success of the Ashy prinia might be due to monogamous parental cares in which both parents maintained the microclimatic condition of the nest from incubation period to chick fledgling.